Salidroside Attenuates Cognitive Dysfunction in Senescence-Accelerated Mouse Prone 8 (SAMP8) Mice and Modulates Inflammation of the Gut-Brain Axis - Xie, Zeping; Lu, Hui; Yang, Sixia; Zeng, Yi; Li, Wei; Wang, Linlin; Luo, Guanfeng; Fang, Fang; Zeng, Ting; Cheng, Weidong (Frontiers in Pharmacology, 2020)
Background Alzheimer’s disease (AD) is a fatal neurodegenerative disease characterized by progressive cognitive decline and memory loss. However, several therapeutic approaches have shown unsatisfactory outcomes in the clinical setting. Thus, developing alternative therapies for the treatment of AD is critical. Salidroside (SAL) is critical, an herb-derived phenylpropanoid glycoside compound, has been shown to attenuate lipopolysaccharide (LPS)-induced cognitive impairment. However, the mechanism underlying its neuroprotective effects remains unclear. Here, we show that SAL has a therapeutic effect in the senescence-accelerated mouse prone 8 (SAMP8) strain, a reliable and stable mouse model of AD. Methods SAMP8 mice were treated with SAL, donepezil (DNP) or saline, and cognitive behavioral impairments were assessed using the Morris water maze (MWM), Y maze, and open field test (OFT). Fecal samples were collected and analyzed by 16S rRNA sequencing on an Illumina MiSeq system. Brain samples were analyzed to detect beta-amyloid (Aβ) 1-42 (Aβ1-42) deposition by immunohistochemistry (IHC) and western blotting. The activation of microglia and neuroinflammatory cytokines was detected by immunofluorescence (IF), western blotting and qPCR. Serum was analyzed by a Mouse High Sensitivity T Cell Magnetic Bead Panel on a Luminex-MAGPIX multiplex immunoassay system. Results Our results suggest that SAL effectively alleviated hippocampus-dependent memory impairment in the SAMP8 mice. SAL significantly (1) reduced toxic Aβ1-42 deposition; (2) reduced microglial activation and attenuated the levels of the proinflammatory factors IL-1β, IL-6, and TNF-α in the brain; (3) improved the gut barrier integrity and modified the gut microbiota (reversed the ratio of Bacteroidetes to Firmicutes and eliminated Clostridiales and Streptococcaceae, which may be associated with cognitive deficits); and (4) decreased the levels of proinflammatory cytokines, particularly IL-1α, IL-6, IL-17A and IL-12, in the peripheral circulation, as determined by a multiplex immunoassay. Conclusion In summary, SAL reversed AD-related changes in SAMP8 mice, potentially by regulating the microbiota-gut-brain axis and modulating inflammation in both the peripheral circulation and central nervous system. Our results strongly suggest that SAL has a therapeutic effect on cognition-related changes in SAMP8 mice and highlight its value as a potential agent for drug development.